Multistable Composite Laminate Grids as a Design Tool for Soft Reconfigurable Multirotors - Luca Girardi; Giada Risso; Laura Pesaresi; Paolo Ermanni; Stefano Mintchev (Advanced Intelligent Systems, 2025)
Adaptive‐morphology multirotors exhibit superior versatility and task‐specific performance compared to traditional multirotors owing to their functional morphological adaptability. However, a notable challenge lies in the contrasting requirements of locking each morphology for flight controllability and efficiency while permitting low‐energy reconfiguration. A novel design approach is proposed for reconfigurable multirotors utilizing soft multistable composite laminate airframes. These airframes show kinematically determinate morphologies corresponding to multiple minima in their elastic potential energy landscape. By varying design parameters, the methodology allows for tuning the energy landscape characteristics governing each morphology's structural stability and reconfiguration energetics. The airframe, composed of multistable composite laminate grids, is optimized to maximize rigidity under flight loads and minimize reconfiguration work. The 130‐g reconfigurable multirotor design demonstrates self‐locking properties in an open and a folded configuration, enabling a 48% reduction in width‐span without compromising stability during flight. Soft pneumatic actuators, actuated using a tethered compressed air supply, enable reversible reconfiguration on the ground between open and folded configurations. The design resolves the conflicting requirements of high‐stiffness to lock each flight configuration and low‐actuation work for reconfigurability. By exploiting soft yet multistable structures, the approach combines the stability observed in rigid‐linked reconfigurable multirotors with the low‐effort reconfigurability of soft multirotors, offering new methods for designing adaptive‐morphology multirotors.